Trends of increase in western medical services in traditional medicine hospitals in china - Moseley Charles B; Lu Jun; Lin Fang; Wang Ying; Shen Jay J; Sun Mei; Hao Mo (BMC, 2011)
Abstract Background Compare changes in types of hospital service revenues between traditional Chinese medicine (TCM) hospitals and Western-medicine based general hospitals. Methods 97 TCM hospitals and 103 general hospitals were surveyed in years of 2000 and 2004. Six types of medical service revenue between the two types of hospitals were compared overtime. The national statistics from 1999 to 2008 were also used as complementary evidence. Results For TCM hospitals, the percentage of service revenue from Western medicine increased from 44.3% to 47.4% while the percentage of service revenue from TCM declined from 26.4% to 18.8% from 1999 to 2004. Percentages of revenue from laboratory tests and surgical procedures for both types of hospitals increased and the discrepancy between the two types of hospitals was narrowed from 1999 to 2004. For TCM hospitals, revenues from laboratory tests increased from 3.64% to 5.06% and revenues from surgical procedures increased from 3.44% to 7.02%. General hospitals' TCM drug revenue in outpatient care declined insignificantly from 5.26% to 3.87%, while the decline for the TCM hospitals was significant from 19.73% to 13.77%. The national statistics from 1999 to 2008 showed similar trends that the percentage of revenue from Western medicine for TCM hospitals increased from 59.6% in 1999 to 62.2% in 2003 and 66.1% in 2008 while the percentage of revenue from TCM for TCM hospitals decreased from 18.0% in 1999, 15.4% in 2003, and 13.7% in 2008. Conclusion Western medicine has become a vital revenue source for TCM hospitals in the current Chinese health care environment where government subsidies to health care facilities have significantly declined. Policies need to encourage TCM hospitals to identify their own special and effective services, improve public perception, increase demand, strengthen financial sources, and ultimately make contributions to preserving one of the national treasures.